Arctic explorations [electronic resource] : the second Grinnell expedition in search of Sir John Franklin, 1853, '54, '55 - Kane, Elisha Kent, 1820-1857 (London : T. Nelson, 1867)
Electronic reproduction. Mode of access: Internet. 44